Stimulating strategies of self-regulated learning for high-school students with learning difficulties - Avram, Olimpia Florentina; Sandu, Mihaela Luminița; Mocanu, Ana-Maria (Technium Social Sciences Journal, 2021)
In the actual contemporary society there are more and more children with disabilities, and the most frequently requested are the Special Educational Needs (SEN), associated with other disabilities that are unnoticed until advanced ages and this because some parents refuse to realise the situation in which their child is. The prevalence of learning disabilities has increased significantly. This is one of the reasons for choosing this topic which is still relevant, the applicability is increasing both in the social system and in the education subsystem. The main objective of this paper is to highlight the learning difficulties that students face in high school. On the other hand, another objective is to illustrate the stimulating strategies for self-regulated learning and assessment. In some cases, age-specific difficulties arise during this period due to the dynamic nature of the school climate. From a pedagogical point of view, the emphasis should be on cognitive development, on the skills needed for the social integration of all students, regardless of origin, nationality and development level. Learning involves overcoming barriers, removing obstacles during individual or collective learning (Popa, D., 2013). Almost forgotten for a long time, the pedagogy of children with learning difficulties has seen a significant increase, especially during the recent years. While looking for ways to a successful learning, it should be considered the use of some methods and planning to reduce learning difficulties for students. Considering that school education (school learning) is a dominant exercise through play, especially during childhood, we must also consider the possibility of frequent learning difficulties, especially regarding children.